PENGEMBANGAN E-LKPD MENGGUNAKAN LIVEWORKSHEETS PADA MATERI AKU YANG DISIPLIN UNTUK MENINGKATKAN HASIL BELAJAR SISWA - dandi, Iklam Dandi Anugrah Ramadhan; Annisa Nurramadhani; Yuli Mulyawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop and assess the feasibility of the E-LKPD media using the Liveworksheets Application on the material "I am disciplined", for fourth-grade students of Cigudeg 01 State Elementary School, Bogor Regency. This type of research is Research and Development (R&D) which refers to the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The resulting product was validated by media, language, and material experts, then tested in fourth-grade classes to evaluate their responses. The results of this study indicate that the response of students and teachers to this E-LKPD media is very positive, with a percentage of 94% of assessments while from media experts 90% from language experts 94%, from material lecturers 86% and from material experts 88%. This shows that the E-LKPD media using liveworksheets on the material "I am disciplined" that has been developed has been effective and very feasible to use. The implications of this research are expected to help teachers in learning and can improve the quality of E-LKPD media in schools. Keywords: E-LKPD, liveworksheets, ADDIE